Crystallisation of minerals from concentrated saline dairy effluent. (15th September 2016) - Kezia, K.; Lee, J.; Zisu, B.; Weeks, M.; Chen, G.; Gras, S.; Kentish, S.
Abstract: An understanding of crystallisation within saline effluents is important for the design of both brine crystallisers and brine disposal ponds. In this work, crystallisation of a saline effluent concentrate from the Australian dairy industry has been examined at 22 wt% and 30 wt% total solids and at temperatures between 10 and 70 °C. The precipitation occurs more rapidly at higher temperatures. This trend is dictated by precipitation of calcium phosphate salts, albeit the major constituents of the mixture are NaCl and lactose. The crystallisation induction time can be shortened by introducing cavitation induced by ultrasound. In particular, the use of two short acoustic pulses between 3.7 J/g and 16 J/g at 20 kHz spaced ten minutes apart has maximum impact upon both induction time and crystal size. It is believed that the first ultrasound pulse either generates new nuclei or enhances the mass transfer of solute toward the surface of sub-micron growing crystals. Conversely, the second pulse disrupts the growing crystals and forms secondary nuclei. The ultrasound cannot shift the solution equilibrium and so is not able to improve the low crystal yield. To increase this total yield, further evaporation is necessary. The work provides direction to personnel in the dairy industry of the feasibility of brine crystallisation with respect to energy demand and solid recovery. Graphical abstract: Highlights: Induction time for crystallisation from dairy brine decreases with increasing temperature. Ultrasound successfully shortens the induction time further. The use of double pulse insonation improves performance with lower energy demand. Selective precipitation of calcium phosphate is not possible.